1986
DOI: 10.1007/bf01655534
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gut hormone levels in 37 patients with pheochromocytomas

Abstract: Pheochromocytomas are usually recognized by the effects of overproduction of catecholamines, but there are clinical features that cannot be ascribed to catecholamine excess that may be due to vasoactive peptides. We, therefore, measured blood levels of vasoactive intestinal peptides (VIP), substance P, somatostatin (SS), and motifin in 50 instances in 37 patients with pheochromocytomas-21 malignant, 10 benign intra-adrenal, and 6 ectopic (5 paracardial and 1 perirenal). Hormone levels were considered raised if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…This expression is presumably in the adrenal medulla and is consistent with detection of MLIR in adrenal tissue (Yanihara, 1978) and with the report of elevated circulating motilin levels in a subset of patients with tumors of the adrenal medulla (Vinik et al, 1986). Motilin mRNA was also observed in the kidney.…”
Section: Discussionsupporting
confidence: 84%
“…This expression is presumably in the adrenal medulla and is consistent with detection of MLIR in adrenal tissue (Yanihara, 1978) and with the report of elevated circulating motilin levels in a subset of patients with tumors of the adrenal medulla (Vinik et al, 1986). Motilin mRNA was also observed in the kidney.…”
Section: Discussionsupporting
confidence: 84%
“…PC12 cells were found to show positive immunohistochemical staining with various motilin antisera; RIA of culture extracts confirmed these observations. A recent report documenting elevated plasma motilin levels in patients with pheochromocytomas (Vinik et al, 1986) provides additional evidence that these cells will be a n accurate model to study the nature of some of the motilin-reactivity in the rat. We plan to use this cell line to study motilin expression and regulation with cloned rat cDNAs.…”
Section: Cerebellummentioning
confidence: 97%
“…Variations in the occurrence and activation of such enzymes in the tumour cells could explain the aberrant de¬ grees of sulphation encountered here. Vinik et al (1986) showed that some pheochro¬ mocytomas secrete one or more of the hormones: somatostatin, motilin, substance and VIP to the blood, which could explain some of the great va¬ riety of symptons seen in these patients. There was no opportunity to measure plasma concentrations of CCK and gastrin in the present study, but as the gastrointestinal functions of CCK depend on tyrosine-O-sulphation (Ondetti et al 1970), dyspeptic symptoms owing to CCK overproduction would not be expected.…”
Section: Discussionmentioning
confidence: 98%